Malaria vaccine development: lessons from the field. - Todryk, S; Bejon, P (2009)
Studies and trials in the field are key to the development of a vaccine for malaria. Our limited knowledge of naturally acquired immunity and of transmission dynamics and disease causation in the field imposes limitations on our ability to predict the efficacy of candidate vaccinations, and the eventual outcome on deploying an efficacious vaccine at a population level.